Захист асинхронних електродвигунів побутових приладів від струмів перевантаження з урахуванням нелінійних спотворень фазного струму - Середа, О.Г.; Варшамова, І.С. (Електротехніка і електромеханіка, 2015)
Теоретично досліджена можливість розширення переліку реалізованих захистів в електронних реле максимального
струму на основі результатів цифрової обробки сигналів від датчиків струму шляхом гармонійного аналізу спектру
фазного струму за наявності нелінійних спотворень. Розроблено алгоритм функціонування мікропроцесорного пристрою захисту асинхронних електродвигунів від неприпустимого перегрівання обмоток при струмах перевантаження з урахуванням нелінійних спотворень фазного струму. Теоретически исследована возможность расширения перечня реализуемых защит в электронных реле максимального
тока на основе результатов цифровой обработки сигналов от датчиков тока путем гармонического анализа спектра
фазного тока при наличии нелинейных искажений. Разработан алгоритм функционирования микропроцессорного
устройства защиты асинхронных электродвигателей от недопустимого перегрева обмоток при токах перегрузки
с учетом нелинейных искажений фазного тока. Purpose. Theoretical justification and engineering of induction
motors heat protection method from overload currents taking
into account nonlinear distortion of the phase current and implementation as a microprocessor device functioning algorithm.
Methodology. To solve the problem used the theory of the representing complex harmonic oscillations analog signals expansion
into the oscillation spectrum forming elementary harmonic
components in order to compare their properties by applying the
theory of discrete signals and systems, as well as methods of
spectral analysis and discrete signals filtering. The harmonic
analysis versatility is that any periodic signal may be synthesized from harmonic oscillation of certain amplitude, frequency
and initial phase. A mathematical model for determining the
phase current harmonic content of power supply networks with
isolated neutral and non-linear loads types and, as a consequence, the distortion of sinusoidal phase current change is
developed by multiplying the analog current in time dependency
on the grate delta-function with different sampling intervals, in
which the use of simple and widely used in relay protection
units, in particular electronic overcurrent relays, mathematical
operations of integration squares instantaneous current allows
the most in harmony with the mathematical tools to build other
network protection types. Findings. The necessity to increase
the sensitivity of the induction motors heat protection from overload currents taking into account nonlinear distortion of the
phase currents is proved. By nonlinear distortion harmonic
analysis of the phase currents the motor protection reliability
increasing provided by taking into account the higher harmonic
components of the phase currents, which causes to additional
losses and heating of the stator winding. It uses the simplest and
widely used in protective relaying mathematical apparatus determining of most significant higher harmonics currents RMS.
Originality. A possibility of extending the implemented protection list of electronic overcurrent relays based on the digital
processing of signals from the current sensors is theoretical
research by the harmonious analysis of phase current spectrum
with the nonlinear distortions presence. A new technical solution is proposed that allows in online sliding monitoring mode
to form response time of electronic overcurrent relays for reliable protection of induction motors from overload currents taking into account nonlinear distortion of the phase current. Practical value. A microprocessor protection functioning algorithm
of induction motors is designed against impermissible heating
coils with overload currents taking into account nonlinear distortion of the phase current.